Synergistic effects between electrocatalyst and electrolyte in the electrocatalytic reduction of lignin model compounds in a stirred slurry reactor - Wijaya, Yanuar Philip; Smith, Kevin J.; Kim, Chang Soo; Gyenge, Elod L. (SPRINGER, 2021)
Valorization of biomass-derived substrates via electrocatalytic hydrogenation-hydrogenolysis (ECH) is an attractive approach for selective production of organic chemicals. The electrocatalytic activity is strongly dependent on the surface coverage of adsorbed hydrogen radicals, which is a complex function of the catalytically active surface sites, electrolyte (pH and composition) and electrode potential. The performance of carbon-supported catalysts (Pt/C, Ru/C, Pd/C) was explored in the ECH of phenol and guaiacol in a stirred slurry electrochemical reactor where the cathode and anode compartments were separated by a Nafion (R) 117 membrane. Acid (H2SO4) and neutral (NaCl) catholytes were used. Pt/C showed superior activity in the acid-acid electrolyte pair, while the activity of Ru/C and Pd/C were significantly improved in the neutral-acid catholyte-anolyte pairs. By pairing neutral catholyte and acid anolyte, the anodic protons transported through the membrane can be effectively utilized for ECH reactions. In terms of reaction pathways for guaiacol ECH, ring saturation leading to 2-methoxycyclohexanol was generally the dominant pathway. However, for Pt/C in either 0.2 or 0.5 M NaCl catholyte paired with 0.5 M H2SO4 anolyte the demethoxylation-ring saturation pathway producing cyclohexanol and cyclohexanone was equally competitive at a constant superficial current density of -109 mA cm(-2) and 50 C-0. Efficient reductive upgrading of lignin model compounds can be achieved under mild conditions via electrocatalysis in the slurry reactor by exploiting synergistic effects between the catalyst and electrolyte. [GRAPHICS] .